Enhancing student engagement and learning outcomes through integrated gamified and personalized e-learning strategies in higher education - Zakiyudin, Mohd Zulakhmar; Hasim, Mohamad Sufian (Universiti Teknologi MARA, Sabah, 2025)
The rapid expansion of e-learning in higher education has intensified the need for effective strategies that enhance student engagement and learning outcomes. This review examines integrated gamified and personalized e-learning approaches, synthesizing current literature to explore their impact within higher education contexts. Drawing from diverse empirical studies and theoretical frameworks, the review identifies key elements of gamification, such as motivational and engagement-enhancing mechanisms, and personalization techniques that tailor learning experiences to individual needs. Findings demonstrate that the integration of these strategies synergistically improves student motivation, creativity, retention, digital skills acquisition, and learner satisfaction. However, challenges including technical infrastructure limitations, pedagogical alignment issues, and institutional readiness remain significant barriers to scalable implementation. The review highlights models incorporating collaborative learning and co-design principles that enhance contextual relevance and effectiveness. Future research directions emphasize the necessity for rigorous longitudinal studies, cross-disciplinary applications, and the incorporation of emerging technologies like AI and virtual reality to further optimize these integrated e-learning strategies.